ENTERPRISE INSOLVENCY: THEORETICAL INSIGHT AND CURRENT TRENDS IN LATVIA - Klodāne, Aļona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The insolvency of enterprises is an integral element of free market. Since Latvia regained its independence, this problem has been urgent for Latvia’s economy as well. It has to be noted that the problem of enterprise insolvency is mainly researched as a separate phenomenon, which could be a strong destructive factor for both the national economy and the economy of an individual business entity. However, there is a methodologically distinctive research direction that associates insolvency with the term enterprise crisis. Anyway, it is important to be aware of real situation characteristics. Therefore, the present research identifies and analyses the theoretical frameworks of enterprise insolvency as well as examines the current situation of insolvency cases in Latvia.